A educação pelas antenas da TV: a narrativa histórica da implantação do telensino no Ceará (1973-1979) - Oliveira, Roberta Lúcia Santos de (2014)
This study has as its object the Telensino System in the State of Ceará, in the period between 1973 to 1979. In other words, since the year of its implementation by the end of the 1970s. The first assumption of this research was the personal interest. Another important assumption was the viability of the research, because the relevance of the subject enabled the existence of sources for the research. We can list as another justification for the social and educational importance of this study, so it will contribute to preserving the history and memory of Ceará education, in the 1970s. This study aimed to construct a historical narrative of Telensino System in the State of Ceará, collaborating to preserving the memory of education; to contrast the educational ways and political clashes in deploying such a system, in the 1970s; to identify the political, economic, social and educational scenery of the state of Ceará, in the 1970s, to reflect the implementation of Telensino; to contrast the pedagogical features Telensino system in the light of social subjects intertwined in the process. The research was historiographical nature and also included oral reports. We used in addition to documentary sources, the speeches of interwoven social subjects in the educational process of implementation of Telensino in Ceará, in the 1970s. This dissertation is divided into three chapters: 1) Ceará in the 1970s: socio-economic, political and educational context ; 2) The Telensino as a way to education in Ceará; and 3) The Telensino the light of the subjects who lived the experience. The subjects were chosen because of their involvement with the topic and the research period. For this reason, we used the techniques of semi-structured interviews. The research was conducted in four parts, divided as follows: Historiographical Dialogue, Search Field, transcription of the interviews and the writing of the dissertation. Based on the analysis of documents and interviews, can be noticed that the Telensino reached a much larger audience than it was initially proposed that it was to take education to the farthest municipalities of Ceará and places of difficult access, to supply the lack of qualified teachers, because they not only took teaching of First Grade at these locations, as well as they assisted in the expansion of undergraduate, from the moment on that the disciplines of Basic Course were taught by television. We emphasize, also that the number of individuals served by the system grew throughout the period surveyed.